Mechanics of Cutting and Boring. Part 4. Dynamics and Energetics of Parallel Motion Tools - Mellor,Malcolm (1977)
The report deals with the cutting of rock and similar materials by parallel motion tools. It examines cutting forces and energy requirements, taking into consideration tool geometry, wear, operating conditions, and material properties. After an introductory discussion of terminology, some general principles are outlined, and relevant theoretical ideas on metal cutting and rock cutting are reviewed. The next section, which is the heart of the report, reviews experimental data on the magnitudes and directions of cutting forces. There is a graphical compilation of data, including some from obscure or unpublished sources. The variables covered include chipping depth, rake angle, relief angle, side rake, base angle, tool width, tool compliance, tool speed, tool wear, tool interactions, and material properties. The second major part of the report treats the energetics of cutting. It begins with a short discussion of relevant principles, and continues with a compilation and review of experimental data, covering the same independent variables as the force section. The report ends with a concise summary of general behavior for parallel motion tools. (Author)